2013
DOI: 10.1210/jc.2012-3823
|View full text |Cite
|
Sign up to set email alerts
|

SRGAP1Is a Candidate Gene for Papillary Thyroid Carcinoma Susceptibility

Abstract: Our findings suggest that SRGAP1 is a candidate gene in PTC susceptibility. SRGAP1 is likely a low-penetrant gene, possibly of a modifier type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 28 publications
0
65
0
Order By: Relevance
“…The Rho family small GTPases serve as molecular switches involved in several cellular progresses 33 . It is reported that overexpression of Rho GTPases in cancers was correlated with poor prognosis 34 and that SNPs in the SRGAP1 gene were associated with papillary thyroid carcinoma 35 . As a subfamily of Rho GTPase-activating proteins, SRGAP1 is involved in regulation of the RhoA activity through interacting with CDC42 that has been proven to exert an important role in cancer development 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The Rho family small GTPases serve as molecular switches involved in several cellular progresses 33 . It is reported that overexpression of Rho GTPases in cancers was correlated with poor prognosis 34 and that SNPs in the SRGAP1 gene were associated with papillary thyroid carcinoma 35 . As a subfamily of Rho GTPase-activating proteins, SRGAP1 is involved in regulation of the RhoA activity through interacting with CDC42 that has been proven to exert an important role in cancer development 36 .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the genetic basis, three susceptibility genes have been identified: the NKX2-1 gene (chromosome 14q13.3), which encodes the thyroid transcription factor NKX2-1 (6), DICER1 (chromosome 14q32), which encodes RNaseIII, an enzyme involved in microRNA processing (7) and SRGAP1, which regulates the small G-protein CDC42 (8). In addition, seven chromosomal loci (1p13.2-1q21, 1q21, 2q21, 6q22, 8p23.1-p22, 8q24 and 19p13.2) involved in FNMTC susceptibility have been mapped, but the causal genes remain to be identified (9,10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…One missense variant, R617C, located in the Rho GAP domain, was detected in <1% of sporadic PTC cases and controls. H875 variant was detected in >10% of sporadic PTC and control cases and did not show any significant differences between PTC cases and controls (He et al 2013a).…”
Section: :12mentioning
confidence: 78%
“…A genome-wide linkage analysis, using SNP genotyping, performed in 38 FNMTC families with PTC identified this 12q14 locus in 21 families with a posterior probability of linkage (PPL) score of 0.3 (He et al 2013a). This implies that there is a 30% probability of linkage of FNMTC to 12q14 locus.…”
Section: Srgap1mentioning
confidence: 99%
See 1 more Smart Citation